COMMUNICATING WAR AND PEACE: THE CONSEQUENCES OF MEDIA IMPERIALISM AND CULTURAL CONFLICT : . - Prasad, Kiran (Journal of Dharma, 2002)
The twentieth century was marked by technological innovations of revolutionary scope and scale leading to digital transformation of the communication landscape, technological convergence, worldwide media coverage and globalization of media content. The post World War II period has witnessed a growing role for the mass media of almost every country in international relations, an intensification of ideological struggle and a tremendous expansion of global information technologies (Frederick, 1993: 217).